How and why do small firms manage interest rate risk☆ - VICKERY, J (Journal of Financial Economics, 2008)
Although small firms are particularly sensitive to interest rates and other shocks, empirical work on corporate risk management has focused instead on large public companies. This paper studies fixed-rate and adjustable-rate loans to see how small firms manage their exposure to interest rate risk. Credit-constrained firms are found to match significantly more often with fixed-rate loans, consistent with prior research that shows the supply of credit shrinks during periods of rising interest rates. Banks originate a higher share of adjustable-rate loans than other lenders, ameliorating maturity mismatch and exposure to the lending channel of monetary policy. Time-series patterns in the fixed-rate share are consistent with recent evidence on debt market timing.